(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Good Health is a secret of every human being. Since the very beginning, Health is a matter of great concern. Some have to, without a choice, maintain a healthy lifestyle by taking medicines. Many patients find it difficult to take medicines at a proper time due to various reasons such as forgetfulness, busy schedule, old age, etc. This happens most commonly with the people taking medicines daily which results in medical non-adherence. Medical Non-adherence is a very serious issue as it can lead to various health-related problems. The advancement in mobile technology has enabled various techniques to solve these types of problems by designing and developing an application which patient will find it easy to carry along. In this paper, we aim to build an Android-based application, that will cover major features such as Medicine Reminder, Medicine Restocking Alert, Alarm System, etc. This system has a rich GUI and easy navigation which can be used by people of every age. This app will have a positive impact on people as it will act as a companion that can display reminders and notify the user to take the pills on time supporting medical adherence and improving health.